2009
DOI: 10.1038/jid.2008.304
|View full text |Cite
|
Sign up to set email alerts
|

IL-10-Producing Langerhans Cells and Regulatory T Cells Are Responsible for Depressed Contact Hypersensitivity in Grafted Skin

Abstract: Although skin grafting is a common surgical technique, the immunological state of grafted skin remains unelucidated. An experimental model has shown that the development of murine contact hypersensitivity (CHS) is depressed when mice are sensitized with a hapten through full-thickness grafted skin. We explored the immunological mechanisms underlying this hyposensitization, focusing on the fate of Langerhans cells (LCs). When FITC was applied to grafted skin, FITC-bearing LCs were capable of migrating to the dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 42 publications
1
43
0
Order By: Relevance
“…Whereas murine keratinocytes are capable of releasing IL-10 (50, 52), human keratinocytes are an unlikely source of IL-10 following in vivo UVB exposure, as they express little mRNA for IL-10 and secrete no IL-10 protein (14). We have previously reported that IL-10-producing LCs in the grafted skin have a crucial role in the induction of Ag-specific Tregs (44). Together with the present finding, it is suggested that the LCs that migrate from the skin to the DLNs are the important source of IL-10 under the condition of UVB irradiation or skin grafting.…”
Section: Discussionsupporting
confidence: 69%
“…Whereas murine keratinocytes are capable of releasing IL-10 (50, 52), human keratinocytes are an unlikely source of IL-10 following in vivo UVB exposure, as they express little mRNA for IL-10 and secrete no IL-10 protein (14). We have previously reported that IL-10-producing LCs in the grafted skin have a crucial role in the induction of Ag-specific Tregs (44). Together with the present finding, it is suggested that the LCs that migrate from the skin to the DLNs are the important source of IL-10 under the condition of UVB irradiation or skin grafting.…”
Section: Discussionsupporting
confidence: 69%
“…In murine LC knockout models, LCs were dispensable for the development of CHS reactions (50) or even exhibited downregulatory properties (51). Induction of Tregs, as observed in different murine models of CHS (16)(17)(18) and in patients with LC histiocytosis (52), is one possibility for the tolerogenic potential of LCs. In this study, we show for the first time to our knowledge that treatment of contact-allergic patients with oral GCS endows LCs with Tregenhancing properties.…”
Section: Discussionmentioning
confidence: 99%
“…This is also true for epidermal Langerhans cells (LCs) (16)(17)(18). In mice, the interaction of the receptor activator for NF-kB (RANK) with its ligand (RANKL), originally described as regulators of bone remodeling and T cell/DC communication (19), is apparently crucial for the induction of regulatory T cells (Tregs) by LCs (17,18).…”
mentioning
confidence: 99%
“…In the skin IL-10 is produced by keratinocytes, 3 macrophages, and DCs on exposure to contact sensitizer or UV radiation. 8,9 Consequently, IL-10-deficient (IL-10 2/2 ) mice mount exaggerated T H 1 responses and exhibit increased irritant and contact hypersensitivity (CHS) reactions in the skin. 10,11 CHS is a relevant murine model for allergic contact dermatitis, one of the most common occupational diseases in human subjects.…”
mentioning
confidence: 99%